2020
DOI: 10.21203/rs.3.rs-64723/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19: Needs assessment of the pharmacy profession and contributions so far across the Commonwealth

Abstract: BackgroundThe declaration of COVID-19 a pandemic by the World Health Organisation on the 11March 2020 marked the beginning of a global health crisis of an unprecedented natureand scale. The approach taken by countries across the world varied widely, however,the delivery of frontline healthcare was consistently recognised as being central to thepandemic response. This study aimed to identify and explore the issues currentlyfacing pharmacy teams across Commonwealth countries during the COVID-19pandemic. The stud… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 17 publications
2
9
1
Order By: Relevance
“…The difficulties encountered on the road while on essential duties might be attributed to the directives given by the government to the law enforcement agencies during the lockdown approach in the study area. In contrast to the findings of a previous study, two-third of the respondents found it somewhat difficult or very difficult to work effectively during the COVID-19 pandemic [25].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The difficulties encountered on the road while on essential duties might be attributed to the directives given by the government to the law enforcement agencies during the lockdown approach in the study area. In contrast to the findings of a previous study, two-third of the respondents found it somewhat difficult or very difficult to work effectively during the COVID-19 pandemic [25].…”
Section: Discussioncontrasting
confidence: 99%
“…In Nigeria, studies have been conducted on COVID-19 [15,17,[21][22][23][24][25][26][27]. From these previous studies, little or no studies have been conducted on the challenges facing pharmaceutical practices during COVID-19 in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…One of the case studies from the Kingdom of Saudi Arabia reported the lack of a national policy as well as practices and processes at healthcare organizational levels as challenges in implementing telepharmacy [ 37 ]. A case study from 54 Commonwealth countries reported issues with the internet, social isolation, difficulty keeping a regular schedule, difficulty accessing tools, lack of physical workspace and difficulty communicating with co-workers as challenges to telepharmacy [ 40 ]. Reimbursement issues were also noted by one case study from Bangladesh [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…A review article from Sri Lanka recommended the need for appropriate legislation and prescribing protocols, especially for controlled medications [ 44 ]. Case studies also suggested providing training to pharmacists for emergency preparedness and providing educational sessions to the public to reduce telepharmacy skepticism [ 40 , 43 , 49 ]. Other strategies included developing appropriate communication protocols with onsite and offsite team members [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation